Individual Innovation Capability dalam Menciptakan kinerja optimal - Dina Novita (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
A person's ability to innovate in the workplace environment is a major factor in creating an innovative organization. The purpose of this study was to analyze the effect of individual innovation capability on performance with knowledge sharing as a moderating variable. This study used a mixed-method design, namely a mixture of qualitative and quantitative involving 100 creative industry employees in Malang City. Data analysis was performed using Huberman's interactive model and Moderated Regression Analysis (MRA). The results show that individual innovation capability has a significant effect on employee performance and individual innovation capability has a significant effect on employee performance with knowledge sharing as a moderating variable, so that performance will be optimal if employees can innovate, and the success of innovation is highly dependent on the willingness of employees to various knowledge in work experience.